2023
DOI: 10.1002/iid3.979
|View full text |Cite
|
Sign up to set email alerts
|

Targetoid‐like lesions and chilblain‐like erythema manifested on hands and feet: A case of Rowell syndrome from China

Yanqiao Li,
Shi Cheng,
Chuanpeng Ying
et al.

Abstract: Background: Rowell syndrome (RS) is an uncommon condition characterized by erythema multiforme (EM)‐like lesions and lupus erythematosus. It is more common in females, and EM may be the first manifestation of the disease with positive autoantibodies, such as antinuclear antibody (ANA), SSA, SSB and rheumatoid factor. The pathogenesis of RS is unknown and is likely caused by drug induction, ultraviolet exposure and infection. Method: We describe a case of RS from China which presented as characteristic targetoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(13 citation statements)
references
References 15 publications
(27 reference statements)
0
13
0
Order By: Relevance
“…1,11,13 Studies have shown that Belimumab, a human monoclonal antibody directed against the B lymphocyte stimulator, is often considered effective in recalcitrant cases of SLE, although data regarding its use in cutaneous SLE is limited. 1 The response to treatment can be assessed using the levels of certain au-dsDNA, anti-Nucl, anti-His, and anti-C1q), among which anti-dsDNA performs the best when assessing disease activity, as suggested by the researchers Shang et al 3 Our patient was subsequently managed with hydroxychloroquine (200 mg once daily), prednisolone (1 mg/kg/day), steroid ointment, a proton pump inhibitor, and sunscreen cream after the diagnosis. Following the treatment, the skin lesions gradually resolve, as shown in Figures 1-3.…”
Section: Case Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…1,11,13 Studies have shown that Belimumab, a human monoclonal antibody directed against the B lymphocyte stimulator, is often considered effective in recalcitrant cases of SLE, although data regarding its use in cutaneous SLE is limited. 1 The response to treatment can be assessed using the levels of certain au-dsDNA, anti-Nucl, anti-His, and anti-C1q), among which anti-dsDNA performs the best when assessing disease activity, as suggested by the researchers Shang et al 3 Our patient was subsequently managed with hydroxychloroquine (200 mg once daily), prednisolone (1 mg/kg/day), steroid ointment, a proton pump inhibitor, and sunscreen cream after the diagnosis. Following the treatment, the skin lesions gradually resolve, as shown in Figures 1-3.…”
Section: Case Discussionmentioning
confidence: 99%
“…The therapeutic regimen used for RS and the prognosis are similar to those of SLE or DLE that occurs alone. However, the diagnosis becomes challenging when DLE coexists with SLE 3 . The majority of the reported cases showed a satisfactory response to corticosteroids with azathioprine, antimalarial drugs such as chloroquine or hydroxychloroquine, dapsone, or cyclosporine 1,11,13 .…”
Section: Case Discussionmentioning
confidence: 99%
See 3 more Smart Citations